The Serum Biomarkers (Serum periostin, IL-5 , IL-13 ) for Predicting Clinical Remission in Severe Asthma: A Systematic Review: Serum Biomarkers in Severe Asthma - Long, Meng; Guo, Fangya; Tu , Siyi; Jiang, Wangyu; Chen, Fang (Journal of Medical Biochemistry, 2026)
Background: Clinical remission is an emerging, ambitious treatment goal in severe asthma, characterized by sustained absence of symptoms and exacerbations, and normalization of lung function while off or on minimal treatment. Easily accessible predictors are needed to guide therapy. Serum biomarkers represent promising candidates. Objective: To systematically review and synthesize the evidence on the association between serum biomarker levels and the achievement of clinical remission in patients with severe asthma. Methods: We searched PubMed, Embase, and Cochrane Central Register of Controlled Trials from inception to October 2025 for observational studies and clinical trials that reported on serum biomarkers and a predefined outcome of clinical remission in severe asthma. Study quality was assessed using the Newcastle-Ottawa Scale. Results: 18 studies (n=4,250 patients) were included. Key biomarkers studied were serum eosinophil count (sEOS), periostin, IgE, and specific cytokines. Higher baseline sEOS was consistently associated with a greater likelihood of achieving remission on biologic therapy (OR 2.1, 95% CI 1.5-2.9). A baseline sEOS ≥150 cells/μL was the most robust predictor . Serum periostin showed a modest positive association (OR 1.6, 95% CI 1.1-2.3), while total IgE was not predictive (OR 1.0, 95% CI 0.8-1.3). Emerging biomarkers like IL-5 and IL-13 receptor levels showed promise but evidence was limited. Conclusion: Current evidence supports serum eosinophil count as a significant predictor of clinical remission in severe asthma, particularly for patients initiating specific biologic therapies. Serum periostin may have a secondary role. Standardized definitions of remission and prospective validation are required for clinical implementation.